2021
DOI: 10.1148/radiol.2021202043
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts in Intracranial Interstitial Fluid Transport and the Glymphatic System: Part I—Anatomy and Physiology

Abstract: Normal physiologic function of organs requires a circulation of interstitial fluid to deliver nutrients and clear cellular waste products. Lymphatic vessels serve as collectors of this fluid in most organs; however, these vessels are absent in the central nervous system. How the central nervous system maintains tight control of extracellular conditions has been a fundamental question in neuroscience until recent discovery of the glial-lymphatic, or glymphatic, system was made this past decade. Networks of para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 101 publications
0
38
0
Order By: Relevance
“…The Monro–Kellie doctrine would predict that under normal conditions, the total volumes of the CSF, brain, and cerebral blood are constant values in the long term. However, recent observations have shown that the Monro–Kellie doctrine is likely not correct ( Mascarenhas et al, 2012 ; Klostranec et al, 2021 ). It can be still deduced from this doctrine that the cerebral blood volume involves the volume changes of the brain and CSF.…”
Section: Discussionmentioning
confidence: 99%
“…The Monro–Kellie doctrine would predict that under normal conditions, the total volumes of the CSF, brain, and cerebral blood are constant values in the long term. However, recent observations have shown that the Monro–Kellie doctrine is likely not correct ( Mascarenhas et al, 2012 ; Klostranec et al, 2021 ). It can be still deduced from this doctrine that the cerebral blood volume involves the volume changes of the brain and CSF.…”
Section: Discussionmentioning
confidence: 99%
“…And studies revealed that AQP4 deficient animals displayed higher levels of CNS water content than control animals at a later phase of CNS injury ( 5 ). AQP4 is the most abundant aquaporins in the brain, it has a polarized distribution tendency on the astrocyte endfeet facing vessels under physiological conditions, this distribution tendency is critical for the formation and resolution of edema, and clearance of interstitial solutes in the brain ( 6 ). Commonly, methods of inhibiting AQP4 mainly include gene knockout, small interfering RNA, heavy metal ions, and small molecule inhibitors ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral capillaries, the site of metabolism, along with the supply of oxygen and glucose, is also the site of metabolic product disposal [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Specifically, it is easy to conceive that astrocytes in contact with the capillaries utilize the Virchow–Robin space, their outer lumen, for disposal.…”
Section: Glymphatic System and Cerebral Circulation And Metabolismmentioning
confidence: 99%
“…Specifically, it is easy to conceive that astrocytes in contact with the capillaries utilize the Virchow–Robin space, their outer lumen, for disposal. Of particular interest is the glymphatic system (GS) as an excretory system for amyloid-β and phosphorylated tau proteins; it is well known that impaired activity of the GS leads to increased amyloid-β production and extracellular accumulation in the brain, and it is well known that, eventually, intracellular phosphorylated tau accumulation leads to neuronal death and Alzheimer’s disease [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. It is not yet clearly understood if a distinction can be made between substances specifically excreted via the GS and those supplied and excreted by the normal arteriovenous system.…”
Section: Glymphatic System and Cerebral Circulation And Metabolismmentioning
confidence: 99%